2014
DOI: 10.4314/sajas.v43i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Association of polymorphism in Exon 3 of toll-like receptor 4 gene with somatic cell score and milk production traits in Holstein dairy cows of Iran

Abstract: Mastitis is a complex inflammatory disease of the mammary gland that is caused by the invasion of pathogens. This leads to reduced synthetic capacity, compositional changes and increased somatic cell counts (SCC) in milk. Toll-like receptor 4 (TLR4) is a cell surface receptor that recognizes lipopolysaccharides (LPS) of gram-negative bacteria. Its role in pathogen recognition and the subsequent immune response and differential expression of the gene during mastitis have prompted the investigation of TLR4 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
1
14
1
Order By: Relevance
“…The alleles controlled the occurrence of three genotypes (AA, AB and AB) with frequency of 0.40, 0.38 and 0.22. The allele and genotype frequencies obtained in the present study were dissimilar to the findings of Wang et al () and Noori et al () who reported frequencies of 0.42, 0.44 and 0.45 for allele A and 0.58, 0.56 and 0.55 for allele B. Shimizu et al () used the same set of primers for examining the TLR4 gene polymorphism of in 200 Holstein dairy cows from the Obihiro University. In the latter study, only two genotypes (AB and BB) were detected, which is dissimilar to that the denoted genotypes in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The alleles controlled the occurrence of three genotypes (AA, AB and AB) with frequency of 0.40, 0.38 and 0.22. The allele and genotype frequencies obtained in the present study were dissimilar to the findings of Wang et al () and Noori et al () who reported frequencies of 0.42, 0.44 and 0.45 for allele A and 0.58, 0.56 and 0.55 for allele B. Shimizu et al () used the same set of primers for examining the TLR4 gene polymorphism of in 200 Holstein dairy cows from the Obihiro University. In the latter study, only two genotypes (AB and BB) were detected, which is dissimilar to that the denoted genotypes in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Wakchaure et al () cited genetic polymorphism in TLR4 gene and its association with incidences of mastitis in Sahiwal cattle. Noori et al () and Li et al () indicated this association with somatic cell score and milk performance traits in Holstein dairy cows. Zhou et al () reported also that the phenotypic variation in milk traits of dairy cows in pasture‐fed New Zealand (NZ) Holstein‐Friesian × Jersey (HF × J) cross dairy cows was attributed to TLR4 gene polymorphism.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our study was carried out to analyse three polymorphisms of the TLR4 gene and to determine their possible associations with SCC and milk composition traits in Holstein cows. Noori et al (2013) showed the T allele in c.9421C>T was associated with lower fat percentage and lower SCS when compared to allele C. Our results obtained frequency of allele T dominated in c.9421C>T. Cows homozygous with T allele produced milk with the lower fat content (4.03 %) but lactose content was the biggest (4.62 %) by following homozygous C allele although no reliable associations have been identified. Zhou et al (2017) reported also that the phenotypic variation in milk traits of dairy cows in pasture-fed New Zealand (NZ) Holstein-Friesian× Jersey (HF×J) cross dairy cows was attributed to TLR4 gene polymorphism.…”
Section: Discussionmentioning
confidence: 48%
“…Sharma et al (2006) described an association between TLR4 and lactation persistency in Canadian dairy cattle, while in Irish cattle Beecher et al (2010) found an association between variation in TLR4 and milk fat and protein percentage. In Iranian Holstein cattle Noori et al (2013) described an association between TLR4 exon 3 variation, and somatic cell score and milk-related traits, while Zhou et al (2017) have determined how polymorphisms of the TLR4 gene influences milk fat content in Chinese Holstein cows. Based on the findings of Ogorevc et al (2009) who examined the role of TLR4 in pathogen recognition and subsequent initiation of the inflammatory and immune response, and on differential expression of the gene during mastitis, TLR4 has been proposed as a candidate for increasing mastitis resistance in breeding programs.…”
Section: Introductionmentioning
confidence: 99%